Cost-sharing in Health : An Appropriate Aspiration for Ukraine? - World Bank (Washington, DC, 2022)
Ukraine’s fight for its values and its future has become an inspiration to the democratic world. That fight comes at an unthinkable human cost, and it will likely only sharpen the expectations of a strong state capable of effectively serving its citizens, who are also taxpayers. A pressing problem to be addressed is the widespread, overwhelming, toxic informality of private financing for health care. For citizens who pay for care for an ill family member, often at the risk of becoming impoverished, the lack of accountability of service providers for results or quality is a grave injustice and a clear threat to social cohesion and economic confidence. This note discusses the idea of cost-sharing for publicly funded health care as Ukraine searches for a socially acceptable trade-off in the scale of public health care coverage. The note looks at possible risks to the population’s health and financial protection as well as possible reasons that may be driving individual and government willingness to take these risks. It also provides numerical simulations to answer the practical question of how much revenue could be generated through co-payments, and poses a question of its own, as the Ukrainian saying goes: is the game worth the candles